Calcio, antifascismo e resistenza in Italia - Giuntini, Sergio (Studi sulla Formazione/Open Journal of Education, 2023)
At the beginning of the twentieth century the attitude of the Socialist Party towards football wash hostile but after the publication of the famous article by Antonio Gramsci “Il football e lo scopone” (1918), the Left directed its criticism at the political exploitation the fascist Regime made of football. This led to many valuable players participating in the Resistance movement. Among them: Antonio Bacchetti, Bruno Ballacci, Dino Ballacci, Severino Feruglio, etc.